Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

equation below
5+3(2x - 7) = 5 + 6x - 21​


Equation Below532x 7 5 6x 21 class=

Sagot :

Answer:

True for all x

Any number

Step-by-step explanation:

Answer:

It's True

Step-by-step explanation:

Let's solve your equation step-by-step.

5+3(2x−7)=5+6x−21

Step 1: Simplify both sides of the equation.

5+3(2x−7)=5+6x−21

5+(3)(2x)+(3)(−7)=5+6x+−21(Distribute)

5+6x+−21=5+6x+−21

(6x)+(5+−21)=(6x)+(5+−21)(Combine Like Terms)

6x+−16=6x+−16

6x−16=6x−16

Step 2: Subtract 6x from both sides.

6x−16−6x=6x−16−6x

−16=−16

Step 3: Add 16 to both sides.

−16+16=−16+16

0=0

Answer:

All real numbers are solutions.